Gestus and taboo - Benedičič, Luka (Amfiteater (Ljubljana), 2022)
The paper addresses Brecht’s concept of Gestus and proposes an original reading of it, parallel to Roland Barthes’s semiological theory. It proposes the view that a gesture becomes a Gestus when it is interpellated into myth. It follows that the Gestus also interpellates into relations, which is, at the same time, its connecting and disconnecting power. The author presents some insights from the theory of ritual and unpacks them to identify some of the ritual’s key characteristics that simultaneously correspond to Brecht’s epic theatre. He does this with an awareness of the ontological differences between ritual and theatre and without the intention of locating Brechtian theatre at any specific locus in the ritual-theatre relation. He intends to think about this relation so that it reveals further insights into the conceptual and practical nature of Brecht’s estrangement effect. Finally, the author recognises its experimental and pedagogical power in its persistent, repetitive intervention in social myths and taboos, which is not only a matter of method but also a matter of initiating in and practising a specific ontology.
Keywords: Brecht, Bertolt; eksperiment; epic theatre; epsko gledališče; ethics; etika; experiment; gestus; ideologija; ideology; ritual; taboo; tatu